Review on treatment of craniocervical soft tissues arterovenous malformations and hemangiomas. Issue 1 (December 2016) - Lucatelli, Pierleone; Sacconi, Beatrice; Anzidei, Michele; Bezzi, Mario; Catalano, Carlo
Abstract Vascular malformations include several vascular abnormalities, congenital in most cases, classified according to their dynamic flow characteristics into high-flow and low-flow abnormalities; both types are commonly located in the head and neck region. Imaging modalities such as Echocolor-Doppler, CT, and MRI can be employed in the evaluation of vascular malformations' in order to describe their size, flow velocity, flow direction, and relationship with the surrounding structures, and, even more important, to differentiate between different types of malformations, since treatment modalities differ depending on their nature (low- vs high-flow).